Detection of the regression on hydroxychloroquine retinopathy in optical coherence tomography - Turgut, Burak; Turkcuoglu, Peykan; Koca, Suleyman Serdar; Aydemir, Orhan (Springer, 2009)
Hydroxychloroquine (HCQ) that is widely used in the treatment of the connective tissue disorders can cause retinopathy. The fundus examination of a patient with systemic lupus erythematosus receiving HCQ revealed left incomplete bull's eye and pigmentary changes in macula in the right eye. Repeated visual field tests showed the paracentral and peripheral defects in the right eye and the pericentral ring scotoma in the left eye. Optical coherence tomography (OCT) scans revealed the photoreceptor loss, retina pigment epithelium (RPE) irregularities, and a cyst-like hypo reflective space over RPE layer on the nasal perifoveal region in the left eye. On the ophthalmoscopic examination, the perifoveal pigmentation was not altered after the discontinuation of HCQ. However, the bilateral visual field defects were improved and the photoreceptor destruction and cyst-like hyporeflective space disappeared in the left eye. Mild RPE irregularities remained in both eyes as revealed by OCT scans. Even if OCT is used to evaluate the regression of HCQ retinopathy, it only shows advanced stage of retinopathy.
Keywords: Hydroxychloroquine retinopathy; Optical coherence tomography; Systemic lupus erythematosus